Effect of Initial Graft Tension During Calcaneofibular Ligament Reconstruction on Ankle Kinematics and Laxity. Issue 12 (October 2018) - Sakakibara, Yuzuru; Teramoto, Atsushi; Takagi, Tetsuya; Yamakawa, Satoshi; Okada, Yohei; Shoji, Hiroaki; Kobayashi, Takuma; Fujimiya, Mineko; Fujie, Hiromichi; Watanabe, Kota; Yamashita, Toshihiko
Background: Although a variety of surgical procedures for lateral ankle ligament reconstruction have frequently been reported, little is known about the effects of initial graft tension. Purpose/Hypothesis: The purpose was to investigate the effects of initial graft tension in calcaneofibular ligament (CFL) reconstruction. It was hypothesized that a high degree of initial graft tension would cause abnormal kinematics, laxity, and excessive graft tension. Study Design: Controlled laboratory study. Methods: Twelve cadaveric ankles were tested with a 6 degrees of freedom robotic system to apply passive plantarflexion-dorsiflexion motion and multidirectional loads. A repeated-measures experiment was designed with the CFL intact, CFL transected, and CFL reconstructed with 4 initial tension conditions (10, 30, 50, and 70 N). The 3-dimensional path and reconstructed graft tension were simultaneously recorded. Results: The calcaneus in CFL reconstruction with an initial tension of 70 N had the most eversion relative to the intact condition (mean eversion translations of 1.2, 3.0, 5.0, and 6.2 mm were observed at initial tensions of 10, 30, 50, and 70 N, respectively). The calcaneus also moved more posteriorly with external rotation as the initial tension increased. The reconstructed graft tension tended to increase as the initial tension increased. Conclusion: Ankle kinematic patterns and laxity after CFL reconstruction tended to become more abnormal as the initial graft tension increased at the time of surgery. Moreover, excessive initial graft tension caused excessive tension on the reconstructed graft. Clinical Relevance: This study indicated the importance of initial graft tension during CFL reconstruction. Overtensioning during CFL reconstruction should be avoided to imitate a normal ankle.